PENGARUH KOMPENSASI, MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA DOSEN DAN STAFF DI UNIVERSITAS TEKNOLOGI SUMBAWA - Esti Sardina; Tomy Dwi Cahyono (Jurnal Nusa Manajemen, 2026)
This study aims to analyze the effect of compensation, work motivation, and work environment on the performance of lecturers and staff at Sumbawa University of Technology. The quantitative approach used was a survey method with 100 respondents consisting of lecturers and permanent staff with a minimum tenure of one year. Data were collected through questionnaires and analyzed using multiple linear regression with the help of SPSS software. The results showed that compensation (t = 2.135; p = 0.035), work motivation (t = 2.741; p = 0.007), and work environment (t = 9.190; p = 0.000) had a positive and significant effect on lecturer and staff performance. The work environment had the most dominant influence on performance, followed by work motivation and compensation. These three variables significantly contribute to improving the performance of teaching and administrative staff at Sumbawa University of Technology. These findings indicate that improved performance of lecturers and staff can be achieved through fair compensation policies, strengthening work motivation, and creating a comfortable and supportive work environment.